2016
DOI: 10.1001/jamasurg.2016.0446
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Arterial Disease in Sub-Saharan Africa

Abstract: The prevalence of PAD in sub-Saharan Africa may be equal to or higher than that in high-income countries, exceeding 50% in some high-risk populations. In addition to population-based studies that better define the PAD burden in sub-Saharan Africa, health systems should consider studies and action regarding risk factor mitigation, targeted screening, medical management of PAD, and defining essential vascular care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 59 publications
1
30
1
Order By: Relevance
“…Since 1990, the prevalence, incidence, and mortality have increased worldwide, with the steepest increases seen in SSA [2]. An excellent systematic review in SSA revealed a high burden of morbidity from PAD, diagnosed by an ankle-brachial index (ABI) of <0.9, where prevalence ranged from 3.1% to 24% of adults aged 50 years and older and 39% to 52% of individuals with known risk factors like diabetes and smoking [111]. The findings of community prevalence rates in SSA are similar to high-income countries [112].…”
Section: Peripheral Artery Diseasementioning
confidence: 99%
“…Since 1990, the prevalence, incidence, and mortality have increased worldwide, with the steepest increases seen in SSA [2]. An excellent systematic review in SSA revealed a high burden of morbidity from PAD, diagnosed by an ankle-brachial index (ABI) of <0.9, where prevalence ranged from 3.1% to 24% of adults aged 50 years and older and 39% to 52% of individuals with known risk factors like diabetes and smoking [111]. The findings of community prevalence rates in SSA are similar to high-income countries [112].…”
Section: Peripheral Artery Diseasementioning
confidence: 99%
“…Peripheral arterial disease (PAD) increases cardiovascular morbidity and mortality in 3% to 10% of the global population . It is associated with an increased hypertensive response and decreased calf muscle oxygenation during calf muscle flexion exercise .…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of study in general population on PAD using ABI from West Africa. Johnston et al in their review noted that African's PAD prevalence ranged from 3.1% to 24% of adults aged 50 years and older and 39% to 52% of individuals with known risk factors (eg, diabetes) [5]. In their systematic door-to-door survey, Guerchet et al reported prevalence of 15% and 32.4% in general population over the age of 65 years in Bangui (Central African Republic) and Brazzaville (Congo) [13].…”
Section: Discussionmentioning
confidence: 99%
“…The minimum sample size was estimated to 753 by using Schwartz formula n=1,962 p(1-p)/i2 where p=4% was the reported prevalence of PAD in general population [5] and i=1% was the error risk. The recruitment was systematic for all workers, aged 18 and over, who signed the consent sheet.…”
Section: Study Design Setting and Samplingmentioning
confidence: 99%
See 1 more Smart Citation